HUBUNGAN INDEKS MASSA TUBUH DENGAN USIA MENARCHE PADA SISWI MADRASAH TSANAWIYAH - Namira Zukhrufiyatul Mardhiyah; Nasution, Silvanni (Poltekkes Kemenkes Medan, 2021)
ABSTRACT Introduction: Menarche is the first menstruation experienced by a woman. Menarche generally occurs at the age of 14 years. In Indonesia, from 1970 to 2010, the age of menarche changed from 14.43 years to 13.63 years. This decrease in the age of menarche has been known to have a risk for psychosocial and physical health problems. Based on several previous studies, this decrease in age at menarche has been associated with an increase in BMI. This study aims to determine the relationship between BMI and age of menarche in students of Madrasah Tsanawiyah Negeri 1 Medan. Methods: This study used a cross-sectional study design. The population of this research is the students of Madrasah Tsanawiyah Negeri 1 Medan. The number of samples used in this study were 73 female students. Results and Discussion: The results of this study showed that the average BMI was 20.94 kg/m2 and the average age at menarche was 12 years. The results of statistical tests using the Spearman correlation test found a relationship between BMI and age at menarche with p = 0.000 (p <0.05) and r = -0.612. Conclusion: Based on the results of this study, it can be concluded that the higher the BMI, the faster the occurrence of menarche. It is recommended for students and parents to pay more attention to a balanced nutritional intake. Keywords: Age of menarche, Body Mass Index (BMI), Student